1993
DOI: 10.1172/jci116793
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human beta 1 thyroid hormone receptor and its mutants with DNA and retinoid X receptor beta. T3 response element-dependent dominant negative potency.

Abstract: Mutations in the human beta thyroid hormone receptor (h-TRB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 38 publications
(34 reference statements)
3
34
0
1
Order By: Relevance
“…The ability of the mutant proteins to bind ligand is moderately or severely impaired (Table II). Other studies have shown that mutant receptors retain the ability to bind to DNA (27)(28)(29) either as homodimers (42) or heterodimers with the retinoid X receptor (30). These functional properties correlate with the observation that RTH mutations lie outside the DNA-binding domain and highly conserved motifs (43)(44)(45) that are known to be involved in dimerization.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The ability of the mutant proteins to bind ligand is moderately or severely impaired (Table II). Other studies have shown that mutant receptors retain the ability to bind to DNA (27)(28)(29) either as homodimers (42) or heterodimers with the retinoid X receptor (30). These functional properties correlate with the observation that RTH mutations lie outside the DNA-binding domain and highly conserved motifs (43)(44)(45) that are known to be involved in dimerization.…”
Section: Discussionmentioning
confidence: 87%
“…We and others (27,28) have also shown that the mutant receptor proteins inhibitwild-type receptor action in a dominant negative manner. Importantly, this inhibition has been observed with reporter genes containing not only positive TREs (29)(30)(31), but also the human TSHa promoter (15,28,46), which is negatively regulated by hTR/3. A number of models have been proposed to account for dominant negative inhibition (28,42), but recent studies indicate that artificial mutations that abolish DNA binding or heterodimerization with RXR are able to abrogate dominant negative inhibitory effects with reporter genes containing the hTSHa promoter or positive TREs (47,48).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In vitro-translated TR␤1 and/or Ear-2 was incubated with the labeled oligonucleotides in binding buffer (18,21) in the presence or absence of antibody. For TR␤1, anti-TR␤1 MAb C4 (36) was used; for Ear-2, PC-9 was used.…”
Section: Methodsmentioning
confidence: 99%
“…The T7 expression plasmids used for in vitro transcription/translation were pCJ3 (TRβ1), pJL08 (ED41), pJL06 (MD32), pCJ4 (KD25), pCJ7 (KP24), and pGEM-PV (PV), which have been previously described (6,33,34).…”
Section: Methodsmentioning
confidence: 99%